Functionalized Low Density Polyethylene with Maleinized Hyperbranched Polyester Polyol (2016)
In this work, low density polyethylene (LDPE) was modified in the melt state with a maleinized hyperbranched polyester polyol (HBPAM), using several proportions of dicumyl peroxide (0.5, 1.0, 1.5 and 2.0 %). Infrared analysis showed the signals of OH, C=O, -COOR and -C=C- groups of the HBPAM in the spectra of the functionalized samples (LDPE-g-HBPAM). Grafting degree (GD) was between 9.14 and 9.82 %. Melt flow index of the samples LDPE-g-HBPAM was lower than that of the LDPE, and it did not exhibit dependency on the dicumyl peroxide content and GD. Exceptfor the sample obtained with a 2.0 % of dicumyl peroxide, all melting temperatures of the samples of LDPE-g-HBPAM were similar to that of the LDPE. The melting enthalpy of the samples LDPE-g-HBPAM decreased with the concentration of dicumyl peroxide and GD. The tensile modulus of these samples was higher than that of LDPE, but the elongation at break was lower.